Business executive coaching and female leaders’ authenticity - Belang, Thato (My University, 2020)
This research was inspired by observations on how female leaders in corporate organisations struggle to remain authentic, as they endeavour to navigate and succeed in these male-dominated corporate organisations. Authenticity is referred to as the ability of an individual to firstly be aware of them self and, secondly, always act in a way that is congruent with their core values. The aim of this research was therefore to explore the effect of executive coaching as a tool in the development of female leaders and how it can develop their authenticity in corporate South Africa. Qualitative research was used in this study, and data were collected through semi-structured interviews with 11 female leaders from different industries who had been coached. The findings were derived using thematic analysis. The key findings corroborated previous studies on the challenges and barriers that female leaders continue to face in corporate that hinder their success as leaders and prevent them from consistently showing up authentically. Challenges such as the unfair sub-culture that permeates in corporate organisations, lack of support structure for female leaders and gender stereotyping continue to stand in the way of the development of female leaders. Specifically, findings on executive coaching and enhancement of authenticity of female leaders revealed that executive coaching indeed is an effective tool that not only assists these leaders in heightening their self-awareness in their areas of development, but also helps them in being rooted to the core values and being authentic to establish their leadership presence in their respective organisations. With the current realities of the challenges and barriers that female leaders face in corporate organisations, transformational changes need to take place. It is recommended that the Human Capital function and top executives accentuate business executive coaching and create safe environments for perpetual engagements through deep and nonconventional female-centred dialogues; led by both males and females, so as to adequately and sustainably address the ungoverned corporate cultures.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Business and Executive Coaching to the Faculty of Commerce, Law and Management, School of Business, University of the Witwatersrand, Johannesburg, 2020
Keywords: SDG-8: Decent work and economic growth